Evaluation the Effect of Growth Regulators and Explants Source on Micro Propagation of Moringa Oleifera In Vitro - Huda E. Mahood (Journal of Global Pharma Technology, 2018)
The present study describes a procedure for indirect regeneration of Moringa oleifera using leaves and stems as explants derived from in vitro germinated seedlings grown on Murashige and Skoog (MS) medium supplemented with different concentrations of auxin and cytokinins. The best callus induction was observed on MS medium containing 1.5 mg.L-1Indole-3-butyric acid (IBA) with 1.5 mg.L-16-benzylaminopurin (BAP) on stem explants .However, when callus was transferred onto a maintenance  medium supplemented with different concentrations of IBA (0.0, 1.0, 1.5, 2.0 or 2.5) mg.L-1and BAP (0.0, 1.0, 1.5, 2.0 or 2.5) mg.L-1, for increasing  callus mass, the combination of  1.5 mg.L-1  IBA with 1.0 mg.L-1 BAP resulted in best response in increasing callus fresh weight. A high shoot proliferation percentage was achieved at the combination 1.0 mg.L-1Kinetin (Kin) with 0.4 mg.L-1Naphthalene acetic acid (NAA) recorded (90%).The rooting percentage was 100% for shoots regenerated from callus cultures when MS medium was supplemented with 2.0 mg.L-1 IBA .After acclimatization, 80% of plants were able to survive.Keywords: Moringa oleifera, Indirect organogenesis, Explants, In vitro, Callus.